Parents and caregivers’ perceptions on content and channels of communication on immunization service messages in Anambra state, Nigeria implication for action - Mba, Ijeoma C.; Aniwada, Elias C. (International Journal of Research in Medical Sciences, 2023)
Background: Effective communication is key to ensuring that barriers to childhood vaccination are tackled. Most times the source and content of information fails to deliver the necessary information needed to make proper decision children’s vaccination. This study explored the perception of communication messages and the different channels used in delivering messages on vaccination among parents/caregivers in Anambra State, Nigeria. Methods: A descriptive cross-sectional study was conducted in Anambra State, Nigeria among parents/caregivers with children aged 0-59 months. A multistage sampling method was used. Questionnaire was used for data collection and analyzed using IMB SPSS version 23. Chi square test was used for association at p<0.05. Results: Findings show that the overall awareness and knowledge was very high 306 (95.6%). Majority 216 (67.50%) of the respondents only receive the key immunization messages during campaigns. Most preferred channel of delivery was through religious groups 273 (85.3%). followed by town announcers 270 (84.4%). Overall, 175 (54.7%) were positive on messages given during Immunization campaigns. Higher proportion agreed that immunization messages are better reinforced if both parents are targeted 309 (98.6%). There were statistically significant association of overall awareness and knowledge with age p=0.043, gender p=0.006, educational level <0.001 and occupation p=0.001. There were no statistically significant association of overall perception with characteristics of respondents. Conclusions: Parents/caregivers’ perceptions of immunization messages can influence social change and increase immunization uptake. Both parents of the children should be targeted whenever immunization messages are to be disseminated.